Commercial herbal slimming products: evaluation of heavy metals and microorganism contamination at different batch production - Nur Faizah Abu Bakar; Noraziah Mohamad Zin; Tuan Siti Mastazliha Long Tuan Kechik; Jacinta Santhanam (Penerbit Universiti Kebangsaan Malaysia, 2017)
Herbal-based slimming products which are consumed orally may be contaminated with heavy metals as well as microorganisms. This study aimed to evaluate the safety level of these slimming products by determining heavy metals and microbial contamination in different batch production. Six different brands of herbal-based slimming products (A, B, C, G, H and I) with three different batch productions (1, 2 and 3) were investigated (n =18). Five heavy metals Arsenic, Cadmium, Chromium, Copper and Zinc were determined using an Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The presence of microorganisms was determined by total aerobic count and the bacteria were identified. The samples’ moisture content was determined by calculating the percentage of water loss after drying process. All batches of samples A and B had high content of zinc, over the permissible level of 5ppm while, 6 samples contained Chromium above the permissible level (1.5 ppm). All 3 batches of sample A presented with the highest total daily intake of heavy metals. Bacteria were present in all the samples tested with the highest numbers in samples G, H and A followed by B, I and C. The highest number of fungi was found in product A while product I was free from fungal contamination. Aspergillus spp. was the predominant fungus present in the samples. There was a weak correlation between moisture content and bacteria (r = 0.087) and fungal (r = 0.253) presence in the samples. As some herbal slimming products contain heavy metals as well as microorganisms, consumers need to be more vigilant and discerning when selecting products to be consumed.